PERFORMANCE MEASUREMENT OF INFORMATION TECHNOLOGY GOVERNANCE: A CASE STUDY - Johanes Fernandes Andry (Jurnal Sistem Informasi, 2016)
Established in 2001, XYZ Cargo is a Freight Forwarder Service Company specialized in the logistic transportation located in Jakarta. XYZ Cargo has broad experiences in both ocean freight and air freight service and has more than sixty agents of partnership around the world. XYZ Cargo has implemented Information Technology (IT) that covers all key aspects of business processes of the enterprise. It has an impact on the strategic and competitive advantages of its success. Many organizations have started implementing IT governance in order to achieve the collaboration between business and IT. The purpose of this research is to get an overview of performance measurement of the currently-running IT Governance with several aspects to consider such as effectiveness, efficiency, functional unit of information technology within an organization, data integrity, safeguarding assets, reliability, confidentiality, availability, and security. The analytical tool used in this research is the COBIT 5 standard procedure by ISACA. The result of IT Governance based on COBIT 5 in domain EDM, shows average values at the level of 2.0 until 2.7 (managed process) for EDM01, EDM02, EDM03 and 1.3 until 1.7 (performed process) for EDM04, EDM05.